The understanding of core pharmacological concepts among health care students in their final semester. Issue 1 (December 2015) - Aronsson, Patrik; Booth, Shirley; Hägg, Staffan; Kjellgren, Karin; Zetterqvist, Ann; Tobin, Gunnar; Reis, Margareta
Abstract Background The overall aim of the study was to explore health care students´ understanding of core concepts in pharmacology. Method An interview study was conducted among twelve students in their final semester of the medical program (n  = 4), the nursing program (n  = 4), and the specialist nursing program in primary health care (n  = 4) from two Swedish universities. The participants were individually presented with two pharmacological clinically relevant written patient cases, which they were to analyze and propose a solution to. Participants were allowed to use the Swedish national drug formulary. Immediately thereafter the students were interviewed about their assessments. The interviews were audio-recorded and transcribed verbatim. A thematic analysis was used to identify units of meaning in each interview. The units were organized into three clusters: pharmacodynamics, pharmacokinetics, and drug interactions. Subsequent procedure consisted of scoring the quality of students´ understanding of core concepts. Non-parametric statistics were employed. Results The study participants were in general able to define pharmacological concepts, but showed less ability to discuss the meaning of the concepts in depth and to implement these in a clinical context. The participants found it easier to grasp concepts related to pharmacodynamics than pharmacokinetics and drug interactions. Conclusion These results indicate that education aiming to prepare future health care professionals for understanding of more complex pharmacological reasoning and decision-making needs to be more focused and effective.